Removal of Copper(II) from Aqueous Solutions by Flotation Using Limestone Fines as the Sorbent and Oleic Acid as the Surfactant - S.E. Ghazy; S.E. Samra; S.M. El-Morsy (Adsorption Science & Technology)
The removal of toxic copper(II) from aqueous solutions was investigated using limestone fines (LS), which are inexpensive and widespread over the globe, as the effective inorganic sorbent with oleic acid (HOL) as the surfactant. The main parameters (i.e. initial solution pH, sorbent, surfactant and copper concentrations, stirring times, temperature and presence of foreign ions) influencing the sorption and flotation processes were examined. The results obtained showed the removal of more than 98% Cu II at pH 7. It was also found that the addition of sodium and magnesium ions as activators enhanced the efficiency of copper separation. The procedure was successfully applied to recover copper spiked to some natural water samples. A mechanism for sorption and flotation is suggested.